Electrical properties of bistable device based on graphene oxide composited with polyvinylpyrrolidone thin films - Thiwawong, Thutiyaporn; Songkeaw, Potiyan; Onlaor, Korakot; Tunhoo, Benchapol (My University, 2021)
This research studied the bistable properties of synthesized graphene oxide (GO) composited with polyvinylpyrrolidone (PVP). The devices were fabricated using a spin coating process on indium tin oxide (ITO)/glass substrate, and the top electrodes were prepared by thermal evaporation with the device structure of ITO/PVP:GO/Al. The PVP:GO films were characterized by Raman spectroscopy, Fourier-transform infrared spectroscopy, X-ray photoemission spectroscopy, and scanning electron microscopy. The current-voltage (I-V) characteristics of the fabricated device exhibited a maximum ON/OFF current ratio in the order of about 104 at a GO concentration of 4 wt%. The mechanism was explained by fitting with the results of the I-V measurement. Moreover, the retention test of the device was more than 2×104 s. The device showed the important characteristics of memory to be a candidate for data storage.
Keywords: Composite; Graphene oxide; Memory device; Nanomaterials; Polymer